Atmospheric water vapour and its effect on aerosol Extinction at a coastal station – Visakhapatnam - NIRANJAN, K.; BABU, Y. RAMESH (MAUSAM, 1993)
Integrated atmospheric water vapour content. has been evaluated from the spectral optical depths around the PaT band of water vapour by making directly transmitted solar flux measurements at 800, 935 and 1025 nm. The temporal variation of the total precipitable water vapour shows significant seasonal variation with maximum during~ pre-monsoon and monsoon months and minimum during winter months. The integrated content shows a positive correlation with surface humidity parameters and the correlation is better during monsoon months compared to other seasons. The experimentally derived variations of water vapour are compared with the model variations formulated using radiosonde data. The aerosol extinctions derived from the, multi-spectral solar flux measurements in the visible and near IR regions increase with increasing atmospheric water vapour and this increase shows .a seasonal dependence the surface temperature also seems to affect the, aerosol extinction probably through Its effect on the mixing heights.